Policing the Pandemic : How Public Health Becomes Public Order - Fatsis, Lambros (Book collections on Project MUSE., 2022)
Written in the context of the #Blacklivesmatter protests, this book explores why law enforcement responses to a public health emergency are prioritised over welfare provision and what this tells us about the state's criminal justice institutions.